Recurrent YAP1 and KMT2A Gene Rearrangements in a Subset of MUC4-negative Sclerosing Epithelioid Fibrosarcoma. (March 2020) - Kao, Yu-Chien; Lee, Jen-Chieh; Zhang, Lei; Sung, Yun-Shao; Swanson, David; Hsieh, Tsung-Han; Liu, Yun-Ru; Agaram, Narasimhan P.; Huang, Hsuan-Ying; Dickson, Brendan C.; Antonescu, Cristina R.
Abstract : Sclerosing epithelioid fibrosarcoma (SEF) is an aggressive soft tissue sarcoma, characterized by a distinctive epithelioid phenotype in a densely sclerotic collagenous stroma, that shows frequent MUC4 immunoreactivity and recurrent gene fusions, often involving EWSR1 gene. A pathogenetic link with low-grade fibromyxoid sarcoma (LGFMS) has been suggested, due to cases with hybrid morphology as well as overlapping genetic signature. However, a small subset of SEF is negative for MUC4 and lacks the canonical EWSR1 / FUS gene rearrangements. Triggered by the identification of recurrent YAP1 - KMT2A gene fusions by RNA sequencing in 3 index cases of MUC4-negative, EWSR1 / FUS fusion-negative SEF, we further investigated a cohort of 14 similar SEF cases (MUC4-negative, EWSR1 / FUS fusion-negative) by fluorescence in situ hybridization (FISH), reverse transcription-polymerase chain reaction, and/or DNA-based massively parallel sequencing (MSK-IMPACT) for abnormalities in these genes. Three additional SEFs with KMT2A gene rearrangements and one additional case with YAP1 gene rearrangements were identified by FISH. In addition, one case with YAP1 - KMT2A and one with KMT2A - YAP1 fusion were detected by reverse transcription-polymerase chain reaction and MSK-IMPACT, respectively. As a control group, 24 fibromyxoid spindle cell tumors, diagnosed or suspected as fusion-negative LGFMS, were also tested for YAP1 and KMT2A abnormalities by FISH, but none were positive. The YAP1 / KMT2A -rearranged SEF group affected patients ranging from 10 to 86 years old (average and median: 45) of both sexes (4 females, 5 males). The tumors involved somatic soft tissues with a wide distribution, including extremities, trunk, neck, and dura. Histologically, the tumors showed variable cellularity, with monotonous ovoid to epithelioid tumor cells and hyalinized collagenous background typical of SEF. More than half of the cases showed infiltrative borders, within fat or skeletal muscle. No LGFMS component was identified. All tumors were negative for MUC4 and had an otherwise nonspecific immunophenotype. Of the 6 cases with available follow-up information, 2 had local recurrences, and 2 developed soft tissue and/or bone metastases, including 1 of them died of the disease. Abstract : Supplemental Digital Content is available in the text.